2011
DOI: 10.1177/1933719111404605
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Nicotine Increases Matrix Metalloproteinase 2 (MMP-2) Expression in Fetal Guinea Pig Hearts

Abstract: This study tested the hypothesis that maternal nicotine ingestion increases matrix metalloproteinase (MMP) expression in fetal hearts, which is mediated by the generation of reactive oxygen species. Timed pregnant guinea pigs were administered either water alone, nicotine (200 mg/mL), N-acetylcysteine (NAC), or nicotine plus NAC in their drinking water for 10 days at 52-day gestation (term ¼ 65 days). Near-term (62 days), anesthetized fetuses were extracted, hearts were excised, and left cardiac ventricles sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In this study, antenatal maternal treatment with a glutathione precursor (NAC) was tested, in order to prevent the long‐lasting vascular effects of FGR. Previous studies using diverse models of FGR in guinea‐pigs have demonstrated that maternal treatment with NAC reduces markers of oxidative stress in different cardiovascular tissues . The present results showed that antenatal treatment with NAC was associated with a normal perinatal and post‐natal growth, and endothelial function.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, antenatal maternal treatment with a glutathione precursor (NAC) was tested, in order to prevent the long‐lasting vascular effects of FGR. Previous studies using diverse models of FGR in guinea‐pigs have demonstrated that maternal treatment with NAC reduces markers of oxidative stress in different cardiovascular tissues . The present results showed that antenatal treatment with NAC was associated with a normal perinatal and post‐natal growth, and endothelial function.…”
Section: Discussionsupporting
confidence: 70%
“…In the guinea pig fetal heart, prenatal hypoxia increases protein levels of MMP- 9 and activity of MMP-2 (Oh et al 2008) while prenatal nicotine increases protein levels of the active form of MMP-2 (Thompson et al 2011). Since MMP-9 is expressed in the developing hippocampus, we tested whether in utero exposure to hypoxia and/or nicotine increased MMP-9 protein levels in the CA1 region of the fetal hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…After sucrose embedding, the brains were frozen on dry ice and stored at −80°C until processed for immunocytochemistry. On a technical note, the animals were not transcardially perfused with fixative because the peripheral organs including the heart were harvested for a separate study (Thompson et al 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, low birth weight adult guinea pigs have increased stiffness in conduit arteries (Thompson et al . ) along with a decreased NOS‐mediated relaxation that is not further impaired by the exposure to an obesogenic diet (Thompson et al . ).…”
Section: Introductionmentioning
confidence: 99%